School life. Reasons for the controversy of a current problems - Hernández Benítez, Jorge Alexander (2021)
In this text, the words school coexistence and pedagogical strategy are analyzed from their, semantics, epistemological, legal and conceptual perspectives; based on the four fundamental learnings which are considered as the pillars of the universal knowledge; Similarly, the impact they have on human and interpersonal relationships in the school context is taken into account,and how they can be used as references for the development of programs, manuals and other documents that make up the normative frameworks that rule schooling and other educational environments; all of the above is taken into consideration in order to inquire about the origins, evolutions, implications and possible solutions of the conflicts that nowadays occur in Colombianschools. The document also analyzes the democratic component and to what extent its adaptation interacts with school coexistence and its implementation in the educational field. In addition,to substantiate the text, some concepts exposed by various authors are chosen and an analytical relationship is made of their relevance to the investigative process, starting from the contexts in which these initiatives would take place, thus generating expectations and ideas for the development of projects aimed at the mediation of personal relationships in favor of the improvementof the school environment and the generation of spaces, democratic, inclusive and of thought.